Telework and Employee Well-Being During the COVID-19 Pandemic: A Two-Wave Survey of Employees at a Texas Health Sciences University - Aro Choi; David Gimeno Ruiz de Porras; Monica Guidry; Janelle Ríos; Francisco Perez; Robert Emery; Luis Ostrosky-Zeichner; George Delclos (Archivos de Prevención de Riesgos Laborales)
Introduction: In the United States (U.S.), the COVID-19 pandemic accelerated the incorporation of telework at academic institutions, but its effect on employee well-being has been insufficiently studied. This study aimed to identify telework-related risk factors and assesses their associations with employee well-being during the pandemic.